Pour la renaissance des villages abandonnés: Quaker Humanitarian Aid in a France at War - Caballer, Gemma (Quaker studies, 2019)
Pour la renaissance des villages abandonnés was an ambitious project organised by the Quakers in late 1940 - at the height of the Second World War in France - and led by an exiled Catalan, Josep Maria Trias Peitx. The aim of the project was to repopulate abandoned or semi-abandoned villages in southern France with displaced persons mainly from the area of Alsace and Lorraine in the north-east of the country, but also with some exiled Spanish families. A detailed analysis of the plan, which can be considered a paradigm of the Quakers' highly valued self-sufficiency projects, also poses some interesting questions: what obstacles did French authorities (and also the local inhabitants) place in the way of the Quakers and their associates, and how did the Quakers deal with them? What conflicts did the humanitarian drama trigger within the Quaker movement itself?